Intelektual Modernisme Dan Intelektual Salafisme: Upaya Menuju Insan Yang Madani Di Era Divergensi - Achmad Nasrulloh (MASADIR: Jurnal Hukum Islam, 2021)
Abstrak: This study aims to determine the attitudes or intellectual character of modernism and salafism that exist in pesantren academics who are also university students in responding to some of the problems they have encountered. The results of this study indicate that Mambaus Sholihin students use the intellectual character of modernism and salafism in answering several problems, in this case in the form of a view on professional zakat and an analysis of the verses of Q.S At-Taubah. Then in a review of Karl Mannheim's social theory on social action and the meaning of behavior of students of Santri Mambaus Sholihin which contains 3 object meanings. First, the objective meaning is that students of Mambaus Sholihin students have views on several things related to professional zakat and provide. The two meanings are expressive, that they view intellectual modernism as a type of thought that prioritizes rationality from contemporary and classical references that tend to tectulize from the Al-Qur'an and the Prophet's Hadith. The third documentary meaning is that the intellectual character of modernism and salafism has become something that is very inherent in santri students in answering various problems found from classical or contemporary reference sources. Kata Kunci : Intelektual Modernisme, Intelektual Salafisme.